Determinants of Private Saving: A Case of Pakistan - Khan, Tasnim; Gill, Abid Rashid; Haneef, Sobia (Asian Journal of Economic Modelling, 2013)
This paper investigates the impact of demographic factors like age, income, dependency ratio, education of males and females and the economic factor of financial depth on household savings in Pakistan. The results were obtained for time series data of 1975-2008 by applying cointegration analysis. The study concludes that increase in per capita income, expected age, deepening of financial system, increase in years of education of both males and females are positively associated with higher saving rate but increase in dependency ratio has negative impact on saving rate. So in order to increase the rate of savings, there is a need to focus on the deepening of financial system on one hand, and improving the education of males and females, increasing the level of income and expected age and reducing the dependency ratio on the other hand.